2018
DOI: 10.1016/j.clml.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Predictive and Prognostic Markers in Adults With Acute Myeloid Leukemia: A Single-Institution Experience

Abstract: Positive predictors of CR in adult AML include absence of monosomy and induction treatment with 3+7; whereas positive predictors of OS are younger age and absence of monosomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
(48 reference statements)
1
10
0
Order By: Relevance
“…The current result agrees with other data. 5,8,9 Among the 4 positive AML patients for RUNX1/RUNX1T1 fusion gene expression, M2 FAB subtype was revealed in all the cases (100%). The result in the current study is in agreement with that of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The current result agrees with other data. 5,8,9 Among the 4 positive AML patients for RUNX1/RUNX1T1 fusion gene expression, M2 FAB subtype was revealed in all the cases (100%). The result in the current study is in agreement with that of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…High-quality evidence showed that the risk of death was 1.17 times higher when patients 5 years younger were compared with patients 5 years older than the median age (hazard ratio [HR] [95% confidence interval per 5-year increase in age], 1.17 [1.11-1.23]). 29,56,[60][61][62][63][64][65][66][67][68][69][70][71][72] High-quality evidence showed that the risk of death was 1.72 times higher when patients with worse performance status (ECOG score of 21) were compared with those with better performance status (ECOG score of ,2) (HR [95% confidence interval], 1.72 [1.47-2.01]). 60,64,[73][74][75][76][77][78][79][80][81][82][83]123 There was also high-quality evidence showing that the risk of death was 1.59 times higher when patients with more comorbidities (HCT-CI score of 31) were compared with those with fewer comorbidities (HCT-CI score of ,3) (HR [95% confidence interval], 1.59 [1.28-1.98]).…”
Section: Prognosis In Older Adults With Amlmentioning
confidence: 99%
“…Similarly, in another study, age <60 years, favourable cytogenetics, de novo AML and leukocyte count at the time of diagnosis of <4 x 109/L were shown to be associated with higher PFS and OS (20). In another retrospective study of 137 adult AML patients between 2010 and 2015, predictive factors for OS and CR were shown to be age and the presence of monosomy (21). Analysis of survival data in two different studies revealed that age is a highly significant prognostic factor even in cytogenetic risk subgroups (22,23).…”
Section: Discussionmentioning
confidence: 77%